Role, involvement and potential of interleukin-27 as an immunotherapeutic target in murine malaria - Fazalul Rahiman, Siti Sarah (2012)
Interleukin-27 (IL-27) has been known to exert pleiotropic role in many inflammatory-related diseases including parasitic infection. However, its involvement during malaria infection has yet to be elucidated. In this study, the role and involvement of IL-27 during malaria infection was investigated and the effects of modulating its release on the course of the infection, the release of major inflammatory cytokines and the histopathological consequences in major affected organs during malaria were evaluated. Plasmodium berghei (P. berghei) ANKA infection in male ICR mice was used as a model for malaria infection. The mice were inoculated intraperitoneally with 2 x 107 parasite-infected red blood cells (PRBCs) whereas the controls received an equivalent dilution of normal RBCs. The concentration of IL-27 in the plasma of malarial mice measured by means of ELISA, showed persistent elevation of IL-27 right from the early until the late phase of infection and its release is independent of the degree of disease severity. The modulation of IL-27 release was carried out by treatment of malarial mice with recombinant mouse IL-27 (rmIL-27), WSX-1Fc chimera or anti-WSX-1 monoclonal antibody (WSX-1 mAb) intravenously. Inhibition of IL-27 with WSX-1 Fc chimera and WSX-1 antibodies delayed the appearance of physical signs of illness and parasitaemia development and also prolonged the survival of malaria-infected mice. Augmentation of IL-27 with rmIL-27 significantly elevated the release of antiinflammatory cytokine (IL-10) whereas inhibition and neutralisation of IL-27 with WSX-1 Fc chimera and WSX-1 mAb respectively, showed decreased level of IL-10. A significant elevation of pro-inflammatory cytokines (IFN-γ and IL-6) was also observed, both during augmentation and inhibition of IL-27. From the pattern of cytokines release, it can be suggested that IL-27 exerts an anti-inflammatory activity in the Th1 type response by signalling the production of IL-10 during malaria. Histopathological examination performed on internal organs including the brain, lungs, liver, spleen and kidneys of malarial mice showed significant sequestration of PRBCs in the microvasculature of all the major organs of malarial mice. Other significant histopathological changes were also observed in malarial mice such as hyperplasia and hypertrophy of the Kupffer cells in the liver, hyaline membrane formation in the lungs, enlargement of the white and red pulp element followed by the lost of structure of germinal centre in the spleen, and vacuolation of the kidney tubule cells. Treatment with rmIL-27 and WSX-1 Fc chimera failed to show any significant improvement on the histopathological conditions of the organs of malaria-infected mice. Overall, the results suggest that IL-27 is involved during malaria infection and it may play an important anti-inflammatory role during immune response against the disease. Modulation of its release produced a positive impact on inflammatory cytokine production during the infection, suggesting its potential as an immunotherapeutic target in malaria, in which the host may benefit from its inhibition.